1973
DOI: 10.1246/bcsj.46.2356
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of the Solvent Extraction of Metal Complexes. II. The Rate of the Extraction of Iron(III) with Thenoyltrifluoroacetone into Carbon Tetrachloride

Abstract: The rate of the solvent extraction of iron(III) in 4.0 M perchlorate ionic media with 2-thenoyltrifluoroacetone (TTA) into carbon tetrachloride has been measured under various conditions. The rate was found to be first order with respect to the concentration of iron(III) in the aqueous phase, first-order with respect to TTA in the organic phase, but independent and inversely first-order with respect to the hydrogen-ion concentration. From these results, it was concluded that the rate-determining step in this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…[20] is theoretically less rigorous than Eq. [19], but practically it was found that the theoretical curves derived from these two equations are very close within the field of experimental conditions investigated in the present work.…”
Section: Mathematical Modellingsupporting
confidence: 77%
See 1 more Smart Citation
“…[20] is theoretically less rigorous than Eq. [19], but practically it was found that the theoretical curves derived from these two equations are very close within the field of experimental conditions investigated in the present work.…”
Section: Mathematical Modellingsupporting
confidence: 77%
“…The ionic strength was chosen as an experimental parameter in the present kinetic study because of the known sensitivity of the investigated system to salting-out effects, but also because various authors have shown that the addition of electrolytes such as NaCI, LiCI, NaCI0 4 , NaN0 3 , ctc., to a given extraction system, may significantly influence the rate of mass transfer (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). It is of interest that there is no general tendency.…”
Section: Introductionmentioning
confidence: 99%
“…Sekine et al [34] studied the rate of iron(III) extraction with 2-thenoyl-trifluoroacetone (TTA) in carbon tetrachloride under various conditions. They found that in the presence of chloride ion, the extraction rate was accelerated due to the formation of FeCl 2+ species which react more rapidly with TTA than do the Fe 3+ species, and the reactions in the former case were higher than those of the latter by a factor of 28.…”
Section: B Iron(iii) Extraction With D2ehpamentioning
confidence: 99%
“…Although many researchers worked on tantalum extraction using a variety of extractants, information regarding the kinetics of tantalum extraction has rarely been reported. In previous work on metal ion extraction kinetics Biswas, 1979, 1980;Sekine et al, 1973), the rate constants and reaction orders were evaluated by the pseudo rate-constant (q) method which is based on the concentration change in the aqueous phase. In contrast, the recent work on metal ion extraction kinetics have used the flux (F) method by the single drop, RDC, and Lewis cell techniques (Biswas and Mondal, 2003a;Biswas et al, 2005;Javanshir et al, 2011).…”
Section: Introductionmentioning
confidence: 99%